Memahami Wahyu Kristiani melalui Heidegger - Kristiatmo, Thomas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
It has been said that the advance of human reflectivity is a menace to orthodoxy. Some brilliant philosophical ideas have been accused of threatening the teachings of religious institutions. That might be the reason why some thinkers were condemned or even punished by religious institutions. In truth, however, human reflectivity is not always a threat. It, instead, can be a torchlight: it can help reformulate traditional teaching afresh and anew. And this can apply to the thoughts of Martin Heidegger. His investigation of the meaning of Being can be deployed to help shed new light to the way Christians understand the revelation. Understanding truth as aletheia, that is, Being that is revealing itself continuously, paves the path to understand God who is unceasingly revealing Godself. Revelation takes place at an ontological level. Revelation is something that besieges human inevitably. Human should not simply linger within the humdrum banalities of daily business, but instead, should be courageous to penetrate into their authenticity to hear the real whispers of God. KeyWords:*Watchman State, *das Geviert, *otentisitas, *aletheia, *wahyu, *bahasa, *Sang Ada, *degodization, *Eigentlichkeit, *Interrelatedness, *'YangLain’